Phenotypic divergences and variation between genetic collection of tomato, based on heterogeneity and environment (Bioagro, 2023)
The homogeneous improved varieties present little genetic diversity; however, the traditional varieties have high heterogeneity in agronomic characters, fruit composition and have been used in genetic improvement. The objective was to evaluate the variation and phenotypic divergence of three groups of genetic populations with different magnitude of heterogeneity, in response to two greenhouse production cycles. Fourteen triple interpopulation hybrids, four advanced lines and four commercial hybrids were sowed under a randomized block design with four replications. The evaluated variables were plant height at 30, 60, and 90 days after transplant (ddt), number of days to flowering, fruiting and maturation of the first and fifth branch, polar and equatorial diameter, average weight, number of fruits and yield to the fifth branch. ANOVA and means comparison by the Tukey test were performed. Among the genetic populations, the behavior of advanced lines and interpopulation hybrids was similar in plant height, physiological and fruit characters, with favorable significant differences with respect to commercial hybrids. Among genotypes, the days to flowering, fruiting and ripening of fruits from the first to fifth branch were higher in the September 2017-March 2018 cycle compared to the March-July 2017 cycle. In the cycle-genetic population interaction, regarding equatorial diameter, the response of the interpopulation hybrids H-76, H-77, H-79, H-90 and H-98 was outstanding when presenting kidney-type fruits. The results indicate that the effect of the environment or evaluation cycles represented the largest proportion of the total phenotypic variance, followed by the effect of groups of genetic populations and genotypes within genetic populations.
Keywords: Genotype-environment interaction; interpopulation hybrids; phenotypic variability